Anies Baswedan-Muhaimin Iskandar Campaign Communication Strategy in the 2024 Presidential Election: Case Study of the “Ubah Bareng” Movement - Buana, Natasha Adhyswasti Padma; Perdana, Aditya (UI Scholars Hub, 2024)
This study examines the Ubah Bareng volunteer movement, a youth-driven initiative supporting Anies Baswedan-Muhaimin Iskandar (AMIN) in the 2024 Indonesia Presidential Election. While existing research on volunteer movements in electoral campigns often focuses on their role as secondary forces under political party control, this study offers new ground by exploring Ubah Bareng’s position as a primary driver in AMIN’s national campaign. By applying Pippa Norris’s (2000) campaign communication strategy theory, this research investigates how Ubah Bareng collaborates with the official campaign team (Timnas) and political parties to effectively mobilize young voters. Through a qualitative methodology, including in-depth interviews and literature review, the findings reveal that Ubah Bareng’s involvement in the official campaign is closely linked to its relationship with Anies Baswedan, Timnas, and political parties. Thus, Ubah Bareng serves as a platform that integrates volunteers, political parties, and Timnas in designing campaign programs. This relation allows Ubah Bareng to operates independently from the official campaign structure while playing pivotal role in designing and executing campaign strategies. This study further identifies Ubah Bareng’s mixed use of pre-modern and post-modern campaign as its main strategy while its hub model represents a new phenomenon that can prevent fragmentation within electoral volunteer movements. Therefore, this study contributes to the broader understanding of volunteer movements in Indonesian politics, offering insights into their evolving role as central actors in electoral campaign strategy.